2019
DOI: 10.1142/s021773231950055x
|View full text |Cite
|
Sign up to set email alerts
|

Non-flat FRW universe version of Tsallis holographic dark energy in specific modified gravity

Abstract: Among various dark energy models, Tsallis holographic dark energy model shows the dynamical enthusiasm to describe the transition phase of the universe. In this paper, we consider Tsallis holographic dark energy with event and apparent horizon as an infrared cutoff in the framework of dynamical Chern–Simon modified gravity and non-flat FRW universe. We explore Hubble, equation of state and deceleration parameters and found that Hubble parameter lies in the range [Formula: see text] and [Formula: see text] for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Later, Panotopoulos et al [110] studied three interacting dark energy models utilizing dynamical system tools and statefinder analysis, which have the potential to discriminate between various dark energy models. Moreover, the study of THDE model in a non-flat universe within the framework of dynamical Chern-Simon modified gravity has been done in [111] where the authors have found compatibility of Hubble parameter and cosmological evolution of . The values of curvature density parameter has been extracted from the data provided in [113] deceleration parameter with present day observational data.…”
Section: Discussionmentioning
confidence: 99%
“…Later, Panotopoulos et al [110] studied three interacting dark energy models utilizing dynamical system tools and statefinder analysis, which have the potential to discriminate between various dark energy models. Moreover, the study of THDE model in a non-flat universe within the framework of dynamical Chern-Simon modified gravity has been done in [111] where the authors have found compatibility of Hubble parameter and cosmological evolution of . The values of curvature density parameter has been extracted from the data provided in [113] deceleration parameter with present day observational data.…”
Section: Discussionmentioning
confidence: 99%
“…In [28], the authors considered nonextensive thermodynamics with a varying exponent. In the framework of modified gravity, the Tsallis model has been discussed in terms of Brans-Dicke gravity [29,30], dynamical Chern-Simons gravity [31], f (T ) and f (G; T ) gravity [32,33] and many others. We considered this model and its generalization to cosmology on the Randall-Sundrum brane in the paper [34], where we investigated the admissible values of the model parameters at which it agrees with the astrophysical observational data.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations on dynamics of THDE with Hubble horizon as IR cutoff, by assuming power law-exponential form for the scale factor have been studied in [55]. Geometrical evolutionary studies in THDE models with Hubble horizon, future event horizon, and GO scale as IR cutoffs corresponding to different interactions have been explored in [56,57,58,59,60,61,62,63]. Investigations on THDE with GO scale as IR cutoff [64], presuming that this energy density is responsible for inflation, show the potentiality of the model in explaining the early universe.…”
Section: Introductionmentioning
confidence: 99%